Brain dominance pattern and creativity thinking in science among students in Jordan - Al-Mughrabi, Ayat Mohammad; Alnasraween, Mo’en Salman; Altawalbeh, Manal (Knowledge management & e-learning, 2025)
The study aimed to investigate the relationship between students’ prevailing brain dominance pattern and their level of creative thinking in science. The study sample consisted of 850 ninth-grade students in Jordan selected by the cluster random method. The brain control scale and the test of creative thinking in science were used to collect data. The study concluded that the student’s creative thinking level was medium in Jordan. The results also showed that the average scores of students with integrated brain control were higher, statistically significant, than those of students with left and right brain control. The results also showed that there were statistically significant differences between the arithmetic means of creative thinking due to gender and in favor of males.